Benefits of CT Scanning for the Management of Knee Arthritis and Arthroplasty - Sodhi, Nipun; Jacofsky, David J.; Chee, Alexander; Mont, Michael A. (The Journal of Knee Surgery, 2020)
This review investigated the potential value of computed tomography (CT) scans for the evaluation and management of knee arthritis and arthroplasty. Specifically, we evaluated the following: (1) assessment of arthritis within knee compartments, (2) patellofemoral joint assessment, (3) implant sizing prediction, (4) component alignment, (5) soft-tissue protection, and (6) potential concerns with radiation exposure. To compare if CT or X-ray imaging is more accurate and clinically relevant, a search was performed using Boolean search operators and terms: “CT,” “radiograph,” “joint alignment,” “knee,” and “arthroplasty,” which yielded 661 results. Studies were evaluated based on (1) assessment of arthritis within knee compartments, (2) patellofemoral joint assessment, (3) implant sizing prediction, (4) component alignment, (5) soft-tissue protection, and (6) potential concerns with radiation exposure. Correlative and comparative analyses of imaging modalities to pre-, intra-, and postoperative clinical and patient-related factors were performed for the 63 included studies. CT scans were found to better detect medial and lateral arthritic changes, bony deformities, subchondral cysts, and cartilage losses. CT scans were shown to 99% accurately predict prosthetic sizes preoperatively. CT scans can also help better visualize surrounding anatomy, such as the posterior cruciate ligament, and have therefore been linked to better soft tissue protection during total knee arthroplasty. Although radiation is a potential concern, newer imaging protocols have comparable exposure to plain radiographs. Compared with plain radiographs, CT scans were found to be more accurate and provide more clinically relevant data. Therefore, the authors recommend the use of CT for the evaluation of certain patients with arthritis and for preoperative planning for knee arthroplasty.
Keywords: CT-scan; X-ray; imaging; total knee arthroplasty; arthritis; knee